2015
DOI: 10.2337/dc15-0360
|View full text |Cite
|
Sign up to set email alerts
|

Results From a European Multicenter Randomized Trial of Physical Activity and/or Healthy Eating to Reduce the Risk of Gestational Diabetes Mellitus: The DALI Lifestyle Pilot

Abstract: OBJECTIVEWays to prevent gestational diabetes mellitus (GDM) remain unproven. We compared the impact of three lifestyle interventions (healthy eating [HE], physical activity [PA], and both HE and PA [HE+PA]) on GDM risk in a pilot multicenter randomized trial. RESEARCH DESIGN AND METHODSPregnant women at risk for GDM (BMI ‡29 kg/m 2 ) from nine European countries were invited to undertake a 75-g oral glucose tolerance test before 20 weeks' gestation. Those without GDM were randomized to HE, PA, or HE+PA. Women… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
89
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(92 citation statements)
references
References 21 publications
3
89
0
Order By: Relevance
“…After signed consent, assessments, including a 75 g OGTT (samples taken at 0, 60, 120 minutes), questionnaire and weight were made before 20 weeks (baseline), between 24-28 weeks (visit 2), between 35-37 weeks (visit 3), and 48 hours post birth as previously described (7,8).…”
Section: Methodsmentioning
confidence: 99%
“…After signed consent, assessments, including a 75 g OGTT (samples taken at 0, 60, 120 minutes), questionnaire and weight were made before 20 weeks (baseline), between 24-28 weeks (visit 2), between 35-37 weeks (visit 3), and 48 hours post birth as previously described (7,8).…”
Section: Methodsmentioning
confidence: 99%
“…All of these may have contributed to the large heterogeneity in the findings. Interestingly, a few studies found an improvement in glucose tolerance in the intervention group, even if no reduction was seen in the risk of GDM [46][47][48].…”
mentioning
confidence: 99%
“…While this study produced large numbers of subjects and statistically significant results it did suffer from only having eight suitable studies and including varying amount of data completed via self-reporting, thus leaving it open to misclassification. Despite this, the study strongly supported the benefits of exercise in pregnant women [7] There are several studies that investigate the reduction of risk of GDM in pregnant women and provide a variable level of evidence [7,8]. A multi-centre randomised controlled trial reviewed women from nine countries [8] and compared physical activity and healthy eating in regards to the risk of GDM.…”
Section: Discussionmentioning
confidence: 99%
“…Despite this, the study strongly supported the benefits of exercise in pregnant women [7] There are several studies that investigate the reduction of risk of GDM in pregnant women and provide a variable level of evidence [7,8]. A multi-centre randomised controlled trial reviewed women from nine countries [8] and compared physical activity and healthy eating in regards to the risk of GDM. The women were randomised into three groups with those undertaking five face-to-face and four optional telephone sessions for either exercises, healthy eating or both.…”
Section: Discussionmentioning
confidence: 99%